Feeding critically ill post Covid-19 patients - Niken Puruhita (World Nutrition Journal, 2022)
Currently, there has been no nutritional therapy guideline available for discharged Covid-19 patients in ICU. Only a small study which was carried in post Covid-19 patients in ICU reported the resting energy expenditure recorded were 20 kcal/kg/day. These number is similar with nutrition therapy recommendations for acute phase critically ill patients provided by ESPEN.